PENERAPAN KONSEP INTERNET OF THINGS (IoT) SEBAGAI MONITORING TEGANGAN DAN ARUS PADA MOTOR INDUKSI 1 PHASE - Heru Susanto; Amir Hamzah (IST AKPRIND Yogyakarta, 2018)
The implementation of technology based on the Internet of Things (IoT) is widely used now and one of them is to monitor a voltage and current on the performance of 1 phase induction motor. Monitoring can be done in real time wherever and whenever using a PC, laptop, and smartphone as long as it is connected to the internet network. This research aims to design, describe the way it works, and implement a voltage and current monitoring system on a 1 phase induction motor using the concept of Internet of Things (IoT). The system is designed using an AC voltage sensor and AC current sensor which is connected to an analog multiplexer using CD4051 whose the output from this multiplexer will be connected to an analog I/O on the NodeMCU which is equipped with ESP8266 as an IoT module. AC voltage and current data will be processed by NodeMCU which will then be displayed on a 2x16 LCD and also published to a Thingspeak that can be stored and downloaded in CSV format. The results of this research has indicated that the design, way of working, and implementation of the monitoring system of voltage and current in a 1 phase induction motor using the IoT concept has been able to display results that are able to display the corresponding voltage and current data between those displayed on the LCD and also published on Thingspeak in real time. The test results show that there is a difference of 5% of the voltage data from the voltmeter with the LCD display and also there is a difference of 16% of the AC amperemeter current data with the LCD display. There is no difference between the voltage and current data displayed on the LCD and Thingspeak even though there is a gap between the time to display data on the LCD and Thingspeak.